Time-Frequency Connectedness between Green Bonds and Conventional Financial Markets: Evidence from China - Yingliang Chen; Guifen Shi; Guanchong Hou (Discrete Dynamics in Nature and Society)
This paper examines the dynamic evolution and volatility spillovers between China’s green bond market and conventional financial markets (bond, stock, commodity, and foreign exchange markets) using time and frequency connectedness measures. The empirical findings are as follows: firstly, there is a significant volatility spillover effect between the green bond market and other traditional financial markets, with the spillover effect showing clear time-varying characteristics. The total spillover effects among all markets increase notably during extreme market conditions. Secondly, the green bond market primarily acts as a net risk spillover transmitter in most periods. Thirdly, compared to the stock, foreign exchange, and commodity markets, the green bond market has a more significant spillover effect on the traditional fixed-income market. Finally, the volatility spillover effect of the green bond market on other markets exhibits a time-frequency evolution, predominantly driven by short-term factors. However, as market maturity increases, the influencing factors of the spillover effect gradually shift from short-term to medium and long-term factors. These findings offer insights for portfolio and risk management.